Countermovement jump performance with increased training loads in elite female rugby athletes - Gathercole, R.; Sporer, B.; Stellingwerff, T. (International Journal of Sports Medicine, 2015)
Countermovement jump (CMJ) performance is typically analyzed through single-point concentric-based variables (e.?g., peak power or force and height). However, methodological approaches examining movement strategies may be more sensitive to neuromuscular fatigue. 12 elite female rugby sevens athletes undertook weekly CMJ testing throughout a 6-week training block involving progressively increased training loads. Athletes self-reported training load (TRIMP) and wellness daily. 22 CMJ variables were assessed, incorporating analyses of force, velocity, power and time measured during eccentric and concentric jump phases. Differences over time were examined using the magnitude of change (effect sizes; ES) compared to baseline. Pearson correlations examined relationships between CMJ variables, wellness and TRIMP. TRIMP displayed large increases (mean ES; weeks 2-6: 2.47). Wellness decreased in week 3 (-0.41), with small reductions following (weeks 4-6: -0.34). Flight time (weeks 3-6: -1.84), peak displacement (weeks 2-6: -2.24), time to peak force (weeks 3-6: 2.58), force at zero velocity (F@0V) (weeks 5-6: -1.28) displayed multiple changes indicative of diminished neuromuscular function. Wellness scores and max rate of force development (mean; r=0.32), F@0V (r=0.28) and flight time (r=0.34) displayed positive correlations. Intensified training decreased CMJ output and altered CMJ mechanics. Longitudinal neuromuscular fatigue monitoring of team-sport athletes appears improved through CMJ mechanics analysis.